2014
DOI: 10.1631/jzus.a1300135
|View full text |Cite
|
Sign up to set email alerts
|

Design criteria for sediment transport in sewers based on self-cleansing concept

Abstract: This study of bed-load transport was undertaken on the basis of laboratory data in two states, i.e., limit of deposition and deposited bed, by using new design criteria, whereby, compared to earlier similar studies, fewer parameters were considered, yet with almost the same or in some cases an even greater level of accuracy. The modified criterion in the new design for transport in the limit of deposition was using only three dimensionless parameters, i.e., Froude number, volumetric concentration of sediment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 23 publications
0
53
0
1
Order By: Relevance
“…According to the table and all indicators, the proposed model produced better results than the regression equations. Among the presented models, most indicators for May et al (1996) equation indicated better results than Ebtehaj et al (2014), but the difference is not significant enough to deem one better than another. It is worth noting that May et al (1996) equation was superior to other equations in terms of MSE, MAE, MARE and d, and a lower R 2 ; therefore, it is quite different from the estimate achieved by May et al (1996), which increases its unreliability.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…According to the table and all indicators, the proposed model produced better results than the regression equations. Among the presented models, most indicators for May et al (1996) equation indicated better results than Ebtehaj et al (2014), but the difference is not significant enough to deem one better than another. It is worth noting that May et al (1996) equation was superior to other equations in terms of MSE, MAE, MARE and d, and a lower R 2 ; therefore, it is quite different from the estimate achieved by May et al (1996), which increases its unreliability.…”
Section: Resultsmentioning
confidence: 84%
“…5. The DR values for ANFIS-DE, and Ebtehaj et al (2014) and May et al (1996) equations are 0.99, 1.03 and 0.97, respectively. Although the difference is not vast, model accuracy and the average precision should be confirmed by considering the maximum relative error values as well.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations